MODERNIZATION OF THE COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS AT BANTEN HIGH SCHOOL - Kurnia, Ukun; Samudi, Samudi; Arifin, Muhammad (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The competence of Islamic education teachers must refer to the guidance of the Prophet Muhammad SAW as a teacher who is equipped with excellent personality traits, cares about social and religious issues, and has a passion for reading, analyzing, researching, and experimenting in various phenomena of life by mentioning the name of Allah, so that he is able to maintain and develop the qualities of faith, righteous deeds, struggle, and cooperation in upholding the truth. Purpose: This study aims to analyze and examine strategies for modernizing the competencies of Islamic religious education teachers. Method: The method used in this study is qualitative with a phenomenological research type, and data collection uses observation, interviews, and documentation, while data analysis uses the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing, while research triangulation uses methodology in the method. Result: The results of this study show that the implementation strategy for modernizing the competency development of Islamic education teachers at Al-Qudwah High School includes: further studies, teacher group formation, discussion programs, seminars and training, weekly monitoring, the dhuha prayer program, literacy, comparative studies, rewards, Al-Qudwah Care, and others. Conclusion: These strategies for modernizing teacher competency have resulted in an improvement in the quality of Islamic education teachers' competencies in the areas of pedagogy, personality, social skills, and professionalism. Meanwhile, the improvement in the competency of Islamic education teachers has ultimately resulted in an improvement in the quality of teaching and learning activities and student achievement.